Animals should definitely not wear clothing - Barrett, Judi (New York : Aladdin Paperbacks, 1970)
Pictures of animals wearing clothes show why this would be ridiculous custom for them to adopt.
Keywords: Animals -- Juvenile humor; American wit and humor, pictorial; Animals -- carricatures and -- cartoons